Tabela
1 41 61
2 3
2
∫ u dv = uv − ∫
v du
21
∫
∫
a 2 + u 2 du =
u 2 a2 a + u 2 + ln u + a 2 + u 2 + C 2 2
( u2 − a2 a du = u 2 − a 2 − a arc cos( ) + C u u
)
∫ ∫
42
u n du 2u n a + bu 2na u n −1du = − ∫ a + bu b(2n − 1) b(2n + 1) a + du
2
n
1
n +i
∫ u du = n + 1u
8
43
+C
22
2 2 2 ∫ u a + u du =
(a u + 2u ) a + u2 −
2 a4 ln u + a + u 2 + C 8
∫
62
3
∫
du = 1n u + C u
23
∫
a2 + u2 a + a2 + u2 du = a 2 + u 2 − a ln +C u u
∫
u − n du a + bu b(2n − 3) u − n +1du =− − n −1 a (n − 1) u 2a (n − 1) ∫ a + bu a + bu 1 1 2 63 ∫ sen (u )du = u − sen (2u ) + C 2 4
2
4
∫ e du = e
44 64
u
u
+C
24
∫
(
(u )du =
45
2
) du u −a du
66
3
∫
∫ cos
u2 − a2 u2 − a2 + ln u + u 2 − a 2 + C du = − 2 u u du = ln u + u 2 − a 2 + C u2 − a2 u 2 du u a2 = u 2 − a 2 + ln u + u 2 − a 2 + C 2 u2 − a2 2
1 1 u + sen ( 2u ) + C 2 4
2 2
5
2
∫ a du = In(a ) a
=
65
2
u
1
u
+C
46
2
25
∫
(
∫u
∫ (u
∫ cot g
67
)
∫ tg
u2 − a2 +C a 2u u
( u )du = tg (u ) − u + C
(u )du = − cot g (u ) − u + C
2
6
∫ sen (u ) du = − cos( u ) + C
26
∫
a2 + u2 a2 + u2 du = − + ln u + a 2 + u 2 + C 2 u u du = ln u + a 2 + u 2 + C a 2 + u2 u 2 du u 2 a2 = a + u 2 − ln(u + a 2 + u 2 ) + C 2 a2 + u2 2
)
∫ sen
68
7 48
∫ u du 2b 3
2 2 2
cos(u ) du = sen (u ) + C
du
1 a2 + u2 + a = − ln +C 27 ∫ a u u a2 + u2
=− +C 3/ 2 − a2 a2 u2 − a2 udu 1 47 ∫ = (a + bu − a ln a + bu ) + C a + bu b 2
( u )du = −
[2 + sen (u)]cos( u) + C
3
2
8
∫ sec (u ) du = tg(u ) + C du 1 u = ln +C 49 ∫ u (a + bu ) a a + bu
50
2 2
2
28
du
=−
∫ a + bu du ln 1 b
[(a + bu ) − 4a (a + bu ) + 2a = ln a + bu
]+ C
∫ cos
69
3
3
[2 + cos (u)]sen (u ) + C udu =
3
∫u
∫ u (a + bu ) = − au + a udu ∫ tg (u )du =
70
3
tg ( u ) + ln cos( u ) + C 2
2
∫ cot g (u )du = −